Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Experimental investigation on seismic performance evolution of reinforced concrete columns considering spatially differential corrosion - Yang Liu; Wei-Ping Zhang; Qian-Qian Yu; Hao-Ran Zuo; Xiang-Lin Gu (Engineering Structures, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Hydraulic performance of circular tunnels with interior drainage boundaries subjected to water level fluctuation - Hao-Ran Lai; Dong-Mei Zhang; Yi-Yao Shen; Bin-Lin Gan (Transportation Geotechnics, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Regulation of sub-Tg solid-state surface crosslinking of reactive polyarylene ether substrate into loose nanofiltration membranes for dyes desalination - Libo Hao; Junni Xie; Lin Pan; Xingbao Yang; Qimeng Ran; Fengfan Gong; Gaolei Zhan; Dongsheng Wang; Xiaobo Liu; Kun Jia (Water Research, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Unveiling the differences between vitexin and isovitexin: From the perspective of sources, green advanced extraction technologies, biological activities, and safety - Jinquan Lin; Hao Ran; Qiqian Feng; Qun Shen; Sumei Zhou; Yuanlin Sun; Dianzhi Hou (Food Chemistry, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Transcriptome analysis reveals the dynamics of gene expression during early embryonic development of hybrid groupers - Fengying Yan; Chongwei Wang; Yuzhi Zhu; Jinhui Wu; JiayuYang; Songyong Gan; Hao Ran Lin; Yong Zhang; Shuisheng Li (Aquaculture, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Peroxymonosulfate-based electrochemical advanced oxidation for pollutant degradation: Roles of Co-phase regulation and electro-induced polarized particle electrodes - Yunlong Liu; Ran Hao; Zhenyu Shi; Wei Zhang; Can Jin; Liang Zhu; Chunmei Tang; Guifeng Liu; Shuping Huo; Lin Xu; Zhenwu Kong (Chemical Engineering Journal, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Gas-to-particle partitioning of atmospheric water-soluble organic aerosols: Indications from high-resolution observations of stable carbon isotope - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Xiao-Ying Yang; Tian Xie; Yu-Xian Zhang; Yongwen Xue (Atmospheric Environment, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Evolution stage identification of haze pollution episodes in beijing using constrained dynamic time warping and multiway principal component analysis - Hao Zhang; Yilun Lin; Jinye Ran; Junyi Yu; Morui Zhu; Hengqi Li; Yongli Jiao (Environmental Modelling & Software, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Transcriptome and DNA Methylation Responses in the Liver of Yellowfin Seabream Under Starvation Stress - Yi Long Lin; Zong Xian Zhu; Chun Hui Ai; Ying Ying Xiong; Tong De Liu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2023)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Urbanization and carbon emission: causality evidence from the new industrialized economies - Khalid Khan; Chi-Wei Su; Ran Tao; Lin-Na Hao (Environment, Development and Sustainability, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Differential Gene Expression Profiles and Alternative Isoform Regulations in Gill of Nile Tilapia in Response to Acute Hypoxia - Hong Lian Li; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Isolation and characterization of 18 microsatellite loci in the Chinese Noctule bat, Nyctalus plancyi - Hao Liu; Yujie Ran; Hongyan Shi; Xiaodong Jia; Lin Zhao (Conservation Genetics Resources, 2015)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Differential expression of glucose-regulated protein 78 during spermatogenesis - Ran Huo; Ye-fei Zhu; Xiang Ma; Min Lin; Zuo-min Zhou; Jia-hao Sha (Cell and Tissue Research, 2004)

Lack of growth hormone-releasing peptide-6 action on in vivo and in vitro growth hormone secretion in sexually immature grass carp (Ctenopharyngodon idellus) - Dong Xiao; Anderson O.L. Wong; Hao-Ran Lin (Fish Physiology and Biochemistry, 2002)